Improving Teachers’ Digital Literacy Competence through Cap Cut-Based Instructional Video Production at SMA Negeri 1 Banyuasin - Nova Yanti Maleha; Juanisa Iriani; Cindi Pramita (Sean Institute, 2025)
The rapid development of digital technology requires teachers to enhance their digital literacy competencies, particularly in developing interactive learning media. However, many teachers still have limited skills in producing video-based instructional materials. This study aimed to analyze the effectiveness of CapCut-based instructional video training in improving teachers’ digital literacy competencies at SMA Negeri 1 Banyuasin. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design involving 25 teachers. Data were collected through a digital literacy competency questionnaire using a five-point Likert scale and analyzed using paired sample t-test. The results showed a significant improvement in teachers’ competencies after the training. The mean score of understanding increased from 1.71 to 4.53 (increase = 2.82), while the mean score of interest increased from 1.74 to 4.37 (increase = 2.63). These findings indicate that hands-on, structured training effectively enhances both technical mastery and positive attitudes toward technology integration in learning. In conclusion, CapCut-based training contributes significantly to strengthening teachers’ digital literacy and supports pedagogical transformation in secondary education. The findings highlight the importance of experiential training models as a practical strategy for sustainable digital competence development in schools.